Java : object-oriented programming concepts (Packt, 2018)
"Java is a mature, elegant and sophisticated object oriented language that runs in a JVM (Java Virtual Machine). Once compiled into byte code, Java can run in a JVM regardless of the underlying environment, Java is 'Write once and run anywhere'. Over the years Java has built for itself the reputation of a language that is capable of delivering high performance robust applications that are elegant, structured and sophisticated. Java is about the Object Oriented way. There are several aspects of the Java language that must be mastered for a developer to use Java at its full potential: The distinction between Classes and Objects, the interaction of Objects and Classes in the forging of an application, the concepts of OO programming (Inheritance and Polymorphism, Abstract Classes and Interfaces, Abstraction and Encapsulation), the memory model, Object identity, the Java Collections framework. You will learn about all these fundamental aspects in this course."--Resource description page